Arab Spring's Impact on the Regional Geopolitics of MENA - Shawkatova, Sara (2025)
This thesis explores the impact of the Arab Spring on regional geopolitics in the Middle East and North Africa (MENA), focusing on how the uprisings transformed the foreign policy strategies of three key regional powers: Saudi Arabia, Iran, and Turkey. Through a comparative case study approach, the thesis traces each country’s pre- and post-Arab Spring foreign policy, with a particular focus on their roles in Yemen, Syria, Iraq, Libya. The findings reveal a regional shift toward interventionism, liquid alliances, and competitive power projection, driven by a combination of regime security concerns, ideological contestation, and changing structural conditions. Despite differing methods and objectives, Saudi Arabia, Iran, and Turkey all pursued more assertive foreign policies aimed at reshaping the regional order in their favor. The thesis concludes that the Arab Spring not only fractured regional cooperation but also redefined traditional power alignments, making the MENA region more fragmented, multipolar, and unstable. These findings contribute to a deeper understanding of Middle Eastern foreign policy and offer insights into the evolving nature of regional dynamics in a post-uprising era.